PENGARUH MEDIA PEMBELAJARAN E-KOMIK BERBASIS KEARIFAN LOKAL TERHADAP KEMAMPUAN LITERASI MEMBACA SISWA KELAS V SDN KARANGDUAK II - Ainatur Rasyika; Alifia Nur Sabilah; Arini Wardatul Istiana; Fahrun Nisak (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to determine the effect of using E-comic learning media based on local wisdom on the reading literacy skills of grade V students of SDN Karangduak II. The research used a quantitative approach with a quasy exprimental desaign method. The research sample was fifth grade students of SDN Karangduak II consisting of experimental and control classes. E-comic learning media was developed by integrating local wisdom values to increase students' engagement and understanding in reading activities. Data were collected through reading literacy test, observation, and documentation. Data were analyzed using statistical tests to determine the significance of differences in learning outcomes between the experimental group using E-comics media based on local wisdom and the control group using conventional learning media. The results showed a significant positive effect of using E-comic learning media based on local wisdom on improving the reading literacy skills of fifth grade students of SDN Karangduak II.